Pseudomonas neustonica sp. nov., isolated from the sea surface microlayer of the Ross Sea (Antarctica). Issue 6 (8th June 2020) - Jang, Gwang Il; Lee, Inae; Ha, Tran Thu; Yoon, Soo Jung; Hwang, Yeon Ju; Yi, Hana; Yun, Sukyoung; Lee, Won Sang; Hwang, Chung Yeon
Abstract : Gram-stain-negative, aerobic and rod-shaped bacterial strains, designated SSM26 T and SSM44, were isolated from a sea surface microlayer sample from the Ross Sea, Antarctica. Analysis of the 16S rRNA gene sequences of strains SSM26 T and SSM44 revealed a clear affiliation with the genus Pseudomonas . Based on the results of phylogenetic analysis, strains SSM26 T and SSM44 showed the closest phylogenetic relationship with the species Pseudomonas sabulinigri KCTC 22137 T with the 16S rRNA gene sequence similarity level of 98.5 %. Strains SSM26 T and SSM44 grew optimally at 30 °C, pH 7.0–7.5 and 0.5–10.0 % NaCl (w/v). The major cellular fatty acids were C18 : 1   ω7 c (31.3–34.9 %), C16 : 0 (15.5–20.2 %), summed feature 3 (C16 : 1   ω7c/C16 : 1   ω6 c ; 19.5–25.4 %) and C12 : 0 (6.0–9.3 %). The genomic DNA G+C content of each strain was 56.2 mol%. Genomic relatedness analyses based on the average nucleotide identity and the genome-to-genome distance showed that strains SSM26 T and SSM44 constituted a single species that was clearly distinguishable from its phylogenetically close relatives. The combined phenotypic, chemotaxonomic, genomic and phylogenetic data also showed that strains SSM26 T and SSM44 could be distinguished from validly published members of the genus Pseudomonas . Thus, these strains should be classified as representing a novel species in the genus Pseudomonas, for which the name Pseudomonas neustonica sp. nov. is proposed with the type strain SSM26 T (=KCCM 43193 T =JCM 31284 T =PAMC 28426 T ) and a sister strain SSM44 (=KCCM 43194=JCM 31285=PAMC 28427).